2019
DOI: 10.1016/j.envpol.2019.113158
|View full text |Cite
|
Sign up to set email alerts
|

Integrative study of microbial community dynamics and water quality along The Apatlaco River

Abstract: The aim of this study is to analyze the water quality parameters and bacterial diversity and thereby understand the effect of water quality on the microbial population structure in the river. The following parameters: total coliforms, chemical oxygen demand, harness, ammonium, nitrite, nitrate, total Kjeldahl nitrogen, dissolved oxygen, total phosphorus, total dissolved solids, and temperature were analyzing along 17 sampling points in the river. The worst levels of pollution were 510 mg/L chemical oxygen dema… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…The following results only concern the microorganisms present in S1-S4 with the potential to carry out bioremediation strategies accordingly to the KEEG analysis. Previous research related to the taxonomy profile of the whole community present at every site can be found at Breton-Deval et al, [13]. Our results suggest that pollution is a selective pressure which enriches the polluted sites with microorganisms with the metabolic capacities to tolerate and transform the contamination (Figure 2b).…”
Section: Pollution and Water Quality In The Apatlaco River Like A Selsupporting
confidence: 61%
See 3 more Smart Citations
“…The following results only concern the microorganisms present in S1-S4 with the potential to carry out bioremediation strategies accordingly to the KEEG analysis. Previous research related to the taxonomy profile of the whole community present at every site can be found at Breton-Deval et al, [13]. Our results suggest that pollution is a selective pressure which enriches the polluted sites with microorganisms with the metabolic capacities to tolerate and transform the contamination (Figure 2b).…”
Section: Pollution and Water Quality In The Apatlaco River Like A Selsupporting
confidence: 61%
“…Daily, Apatlaco River receives 321 different discharges of wastewater from the manufacturing industry, domestic and agro-sector [13]. Our results showed that the water quality throughout the river is associated with the wastewater discharged sites (Table 1), ( Figure 2) according to a chi-square test of independence (X 2 (3, N = 24) = 10.86, p = 0124).…”
Section: Pollution and Water Quality In The Apatlaco River Like A Selmentioning
confidence: 69%
See 2 more Smart Citations
“…Historically, the ecosystems most scrutinized by metagenomic have been host-associated or environmental origin [2,3]. Among the aquatic ecosystems, two of the most neglected biomes involve freshwater and sediments metagenomes, despite the importance of microbial dynamics in the function of freshwater surface bodies [4]. Since 2010, 10,648 metagenomes have been uploaded to the National Center for Biotechnology Information (NCBI) Assembly database, 148 from freshwater environments, and 111 from sediments Often it is difficult to connect the ecological functions that take place in microbiomes with the specific biotypes that perform them.…”
Section: Introductionmentioning
confidence: 99%